Identification of apoptosis-related genes in erythrocytes of broiler chickens and their response to thiram-induced tibial dyschondroplasia and recombinant glutathione-S-transferase A3 protein. (October 2018) - Wang, C.X.; Niu, S.; Jahejo, A.R.; Jia, F.J.; Li, Z.; Zhang, N.; Ning, G.B.; Zhang, D.; Li, H.Q.; Ma, H.L.; Hao, W.F.; Gao, W.W.; et al.
Abstract: Thiram, a carbamate pesticide, is known to induce tibial dyschondroplasia (TD) in broiler chickens. This study used a thiram-induced TD model to explore whether apoptosis-related genes were expressed in erythrocytes of broiler chickens and the impacts of thiram-induced TD and the recombinant GSTA3 protein in regulating these genes expression. In this study, mRNA and protein expression of six types of apoptosis-related genes (Bcl-2, Bax, Murine double minute MDM2, Bcl-2-associated athanogene BAG-1, BAG-3, STAT3) were identified in erythrocytes of broiler chickens by real-time PCR and immunohistochemistry, and we also found that thiram-induced TD induced the decreased expression of these antiapoptotic genes in the initial stage of TD and promoted their expression in TD recovery, which suggested that the expression of these apoptosis-related genes in erythrocytes is highly related to the development of TD. Further, the recombinant GSTA3 protein promoted the expression of all apoptosis-related genes in the initial stage of TD and recovered the normal expression of these genes in the recovery stage of TD, which indicated that the recombinant GSTA3 protein may participate in the recovery of TD. Further studies are needed to elucidate the mechanism of the response of erythrocytes to thiram-induced TD and the recombinant protein GSTA3 in broiler chickens. Highlights: Chicken erythrocytes constitutively express 6 types of apoptosis-related genes at the transcript level. The expression of apoptosis-related genes in erythrocytes is highly related to the development of TD. The GSTA3 protein promoted the expression of all apoptosis-related genes after the occurrence of TD.